HISTOPATOLOGI HATI MENCIT PASCA PEMBERIAN SUSPENSI KEPEL (Stelechocarpus burahol) SECARA INTRAGASTRIK SELAMA 14 HARI The Histopathology of Mice Liver Treated by Kepel (Stelechocarpus burahol) Suspension Intragastrically for 14 days - Harlina, Eva; Sa’diah, Siti; S Darusman, Huda; Alvernita, Gita (FITOFARMAKA | Jurnal Ilmiah Farmasi, 2012)
This aim of this study was to examine the effect of Kepel (Stelechocarpus burahol) to the mice hepatocytes. Thirty male mice of 4 week aged were divided into three groups; control group was treated by aquadest, Dose 1x group was treated by 2.6 mg/g BW/day kepel powder (0.5 ml kepel suspension/day), and Dose 5x group was treated by 13 mg/g BW/day kepel powder (1.0 ml kepel suspension/day). The treatment was intragastrically for 14 days. The mice were euthanized and necropsy followed by the liver collection for histopathology assay. The histopathological examination of liver showed hydropic degeneration, cell death and extramedullary hematopoietic observed on mice hepatocytes. The ANOVA analysis showed that kepel caused increase significantly (p<0.05) of hydropic degeneration and decrease significantly (p<0.05) of cell death of mice hepatocytes.Key words: Stelechocarpus burahol, hydropic degeneration, cell death, extramedullary hematopoietic